THE CONCEPTUAL BASIS OF USING DIGITAL MARKETING TECHNOLOGIES IN DEVELOPMENT OF THE ACTIVITY OF ENTERPRISES (Conferencea, 2022)
The current article provides for the conceptual framework of digital marketing technologies and their vital aspects and usage processes in enterprise, companies by giving primary focus on textile, garment and knitting field. Also, it highlights for the implementation of digital e-textile model of CAD and 3D application technologies for textile, garment enterprises in creating enormous ease of the working process.